Women in Colombian Traditional Coffee Growing, 1910 – 1970. - Bacca, Renzo Ramírez (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article discusses the complex and diverse labor dynamics of women in rural and urban sectors of the Colombian coffee industry. This concise analysis is limited to the production stage of the grain grown under shade, a technique that has been used during a large part of the twentieth century in the Andean region, and highlights the status of women, considering their condition as collectors, sorters or tabloneras.This study has a descriptive and historical approach supported on an extensive documentary archive and secondary sources.